2003
DOI: 10.1093/aob/mcg086
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ultraviolet-B Radiation on Cotton (Gossypium hirsutum L.) Morphology and Anatomy

Abstract: Cotton (Gossypium hirsutum L.) crop, cultivated between 40 degrees N and 40 degrees S, is currently experiencing 2-11 kJ m-2 d-1 of UV-B radiation. This is predicted to increase in the near future. An experiment was conducted to study the effect of enhanced UV-B radiation on vegetative and reproductive morphology and leaf anatomy of cotton in sunlit, controlled environment chambers. From emergence to harvest, cotton plants were exposed to 0, 8 or 16 kJ m-2 d-1 of UV-B in a square wave approach for 8 h from 080… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
96
0
24

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(132 citation statements)
references
References 39 publications
(46 reference statements)
12
96
0
24
Order By: Relevance
“…These results contrast with the findings by SEARLES et al (2001), where one of the most evident response to UV-B radiation observed was an increase in UV-B absorbing compounds. The increase in UV-B absorbing compounds in response to enhanced UV-B radiation reported by several authors has been interpreted as an (KAKANI et al, 2003a). Also, the protective effects of trichomes against UV-B radiation damage have been demonstrated by mechanically removing the trichomes of Verbascum speciosum (MANETAS, 2003).…”
Section: Resultsmentioning
confidence: 91%
“…These results contrast with the findings by SEARLES et al (2001), where one of the most evident response to UV-B radiation observed was an increase in UV-B absorbing compounds. The increase in UV-B absorbing compounds in response to enhanced UV-B radiation reported by several authors has been interpreted as an (KAKANI et al, 2003a). Also, the protective effects of trichomes against UV-B radiation damage have been demonstrated by mechanically removing the trichomes of Verbascum speciosum (MANETAS, 2003).…”
Section: Resultsmentioning
confidence: 91%
“…Resultados similares de menores valores médios de densidade estomática, na face adaxial, foram encontrados para as folhas de Oryza sativa que se desenvolveram sob a ação da radiação UV-B (Dai et al 1995). No entanto, resultados diferentes foram obtidos para algodão, onde folhas tratadas com alta dose de radiação UV-B (16 kJm -2 .d -1 ) apresentaram maiores densidades estomáticas, em ambas as faces, do que as folhas controle (Kakani et al 2003b). Segundo os autores, a radiação UV-B parece afetar as plantas de maneira similar ao déficit hídrico, reduzindo a área foliar e ao estresse térmico, aumentando a densidade estomática.…”
unclassified
“…A folha diminui a área exposta, mas aumenta a espessura da lâmina, devido ao incremento dos tecidos fotossintéticos e dos espaços intercelulares, garantindo assim o volume da folha (Lewis 1972;Smith et al 1997). Maior espessura também foi reportada para outras espécies estudadas sob a influência da radiação UV-B (Cen & Bornman 1993;Kakani et al 2003a), apesar de resultados contrários serem reportados na literatura (Correia et al 1998;Kakani et al 2003b).…”
unclassified
“…Increas ed root biom ass, PA L activit y, r oot dr y weight, s hoot: root rati o, leaf ar ea, c hlor ophyll a, chl orophyll b, and tot al chl orophyll. T his result w as s upport ed with Kakani et al (2003) in various growt h parameters , and other inves tigations, whic h r eport ed a decr eas e i n plant length and leaf area wit h UV radiation (Teramur a et al, 1991;Bar nes et al, 1993;Hao et al, 2000;Z uk-G olasz ewsk a et al , 2003;Li u et al, 2013). This c ontradicti on m ay be due to t he use of higher U V A+ B r adiation.…”
Section: Discussionmentioning
confidence: 77%